2021
DOI: 10.4041/kjod.2021.51.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mandibular buccal shelf characteristics in the Colombian population: A cone-beam computed tomography study

Abstract: Objective To evaluate the mandibular buccal shelf (MBS) in terms of the angulation and bone depth and thickness according to sex, age, and sagittal and vertical skeletal patterns in a Colombian population using cone-beam computed tomography (CBCT). Accordingly, the optimal site for miniscrew insertion in this area was determined. Methods This descriptive, retrospective study included 64 hemi-arches of 34 patients. On CBCT images, the angulation, buccal bone depth (4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
23
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 19 publications
11
23
3
3
Order By: Relevance
“…In the present study, it was found that there were no statistically significant differences in the bone characteristics of the MBP according to the vertical growth pattern. These findings partially agree with those previously reported by Escobar-Correa et al (14) who indicated that the hypodivergent pattern had a tendency to higher values but this difference was not significant.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, it was found that there were no statistically significant differences in the bone characteristics of the MBP according to the vertical growth pattern. These findings partially agree with those previously reported by Escobar-Correa et al (14) who indicated that the hypodivergent pattern had a tendency to higher values but this difference was not significant.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the characteristics of the MBS were also evaluated according to sex and the side of the hermiarch, finding that there were no significant differences in both cases, which coincides with what was previously reported by other authors (14,15). Also, Farnsworth et al (24) observed that there was no difference in the cortical thickness of the mandibular alveolar bone between men and women.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations